Pyridoxine Toxicity in Pediatric Patient with ESRD on Peritoneal Dialysis. Case Report (Global Journal of Medical Research, 2023)
Pyridoxine induced toxicity was first described in 1984 in 58 years old female patient who used megadose as prescribed by her physician to treat carpal tunnel syndrome Later on couple of case report also reported different forms of neurosensory toxicity in adult patients on high doses and or long-term therapy of pyridoxine We present the first case of pyridoxine toxicity in pediatric patient received therapeutic dose of pyridoxine of 1 mg kg day once daily who presented with low blood pressure headache and hypersomnia
Keywords: pyridoxine; children; toxicity